Edwin D. Driver. (comp.). Essays on Population Policy, Lexington, Massachusetts, Lexington Books, D. C. Heath and Company, 1972, 202 p. - Alba Hernández, Francisco (Estudios Demográficos y Urbanos, 1973)
EDWIN D. DRIVER, Comp., Essays on Population Policy, Lexington, Mas-sachusetts, Lexington Books, D. C. Heath and Company, 1972.